Primary malignant giant cell tumor (PMGCT): Diagnosis and management challenges in low resource settings - Prasad, Roshan; Shukla, Samarth; Acharya, Sourya; Mittal, Gaurav; Wanjari, Mayur (Narra J, 2025)
Bone primary malignant giant cell tumor (PMGCT) cases are extremely rare, and the optimal management remains unclear. This case report details the diagnosis and successful management of PMGCT in a 45-year-old female presenting with left knee pain, swelling, and restricted movement for one year. Accompanying weight loss and loss of appetite led the patient to seek tertiary care after unsuccessful prior treatment. Imaging, including X-ray and magnetic resonance imaging (MRI), revealed a tumor measuring 7.9 × 7.7 × 6.6 cm, and histopathological examination using fine needle aspiration cytology confirmed the diagnosis of PMGCT. A multidisciplinary approach was taken, involving orthopedic surgery to remove the tumor successfully, and physiotherapy for post-operative care. The patient underwent tumor excision and curettage under spinal and epidural anesthesia, followed by a week of bed rest, and then physiotherapy was started to aid in limb mobilization. Post-operative care involved blood transfusions, femoral artery stenting, continued physiotherapy and adjuvant radiotherapy, initiated two weeks post-surgery, with a total dose of 50 Gy delivered in 25 sessions to reduce the risk of recurrence. Initial monthly follow-ups, later transitioning to quarterly, showed improved joint mobility and function, with no recurrence at the 9-month follow-up. This case highlights the importance of early diagnosis and a multidisciplinary approach in managing PMGCT. Collaboration across specialties contributed to the positive outcome, even in a resource-limited setting. Long-term monitoring remains essential to detect recurrence, and further research is needed to refine treatment strategies for malignant GCTs.